Effect of heme oxygenase–endogenous carbon monoxide on mortality during septic shock in rats - Yu, J.-b. (Springer-Verlag, 2008)
AIM: To investigate the effect of HO–CO on mortality during septic shock in rats. METHOD: Eighty rats were randomly divided into group-control, group ZnPP-IX, group SS, and group LZ. RESULTS: Death was significantly lower in group SS than in group LZ (P < 0.05). The MAP was significantly higher in the group LZ than in the group SS (P < 0.05). ALT, AST, Cr and BUN, MDA, and the lung EB contents, were significantly lower in the group SS than that in the group LZ (all P < 0.05). And CO and SOD activities were significantly higher in group SS than that in the group LZ (all P < 0.05). HO-1 mRNA, and HO-1 protein were significantly lower in the group LZ than in the group SS (P < 0.05), whereas HO-2 mRNA, and HO-2 protein were not significantly different among four groups (all P > 0.05). CONCLUSION: The increased oxidative stress and end-organ damage is related to mortality during septic shock; while the hypotension partly contributing to HO-1 protein and CO has no obvious relation with it.